Atmospheric dispersion and dose assessment of 137Cs and 131I from hypothetical incidents of nuclear power plant in Southeast Asia. (July 2023) - Muhamad, L.H.; A Karim, M.K.; Chew, M.T.; Kechik, M.M.A.; Shah, N.M.; Ibahim, M.J.; Saeed, I.M.
Abstract: In the event of radiological incidents, specifically nuclear accidents, a substantial quantity of radionuclides may be distributed, resulting in potential cancer hazards and the possibility of death. Hence, it is imperative for governing bodies to replicate hypothetical accidents that may occur from potential nuclear reactors, with the aim of ascertaining the probable dose exposure that the populace may face. The aim of this study was to evaluate the level of dispersion of 131 I and 137 Cs that would ensue from a hypothetical incident scenario of a nuclear power plant (NPP) in Ninh Thuan, Vietnam, and Mersing, Malaysia, by utilizing the HYSPLIT model. The model was set up based on the meteorological conditions in the potential site for NPP located in Southeast Asia. Following the study, a comparison was made between the results and the authorized dose limits proposed by the International Atomic Energy Agency to assess the potential mortality risk arising from an accident. The outcomes revealed that the mean activity concentration for both radionuclides was greater in Mersing than in Ninh Thuan on the initial day of the accident. The activity concentration of 137 Cs and 131 I at Mersing is the highest at 3.34 × 10 2 kBq/m 3 and 2.01 × 10 4 kBq/m 3, respectively. Meanwhile, Ninh Thuan has the highest activity concentration of 137 Cs and 131 I at 2.37 × 10 2 kBq/m 3 and 1.43 × 10 4 kBq/m 3, respectively. Based on these figures, the release of 137 Cs and 131 I at Mersing results in an effective dose of approximately 2.58 × 10 −4 mSv and 0.71 mSv, respectively. Conversely, the release of 137 Cs and 131 I at Ninh Thuan results in an effective dose of approximately 8.21 × 10 −5 mSv and 0.23 mSv, respectively. According to risk assessment, the inhalation of radionuclides poses the highest mortality risk in Mersing, with a rate of 51 out of 100, 000 individuals at altitudes between 0 m and 10 m within 4 h of an accident. Similarly, in Ninh Tuan, the predicted mortality rate due to radionuclide inhalation at the same altitude level is approximately 17 out of 100, 000 individuals. To mitigate the radiological consequences on the population, it is crucial to improve emergency protocols in these regions, taking into account their location and geographical features. This can be achieved through measures such as evacuation, sheltering, and resettlement of the population to safer areas. Highlights: We evaluate the dispersion of 137 Cs and 131 I from a hypothetical NPP incidents in Ninh Thuan, Vietnam, and Mersing, Malaysia. The radionuclide effluent from a nuclear accident would affect neighboring countries. The accumulated dose for the first day of the accident exceeded the limit suggested by the ICRP. The variation in dispersion patterns on the environment also discussed.